4-Aminoindazolyl-dihydrofuro[3, 4-d]pyrimidines as non-covalent inhibitors of mutant epidermal growth factor receptor tyrosine kinase. Issue 2 (15th January 2016) - Hanan, Emily J.; Baumgardner, Matt; Bryan, Marian C.; Chen, Yuan; Eigenbrot, Charles; Fan, Peter; Gu, Xiao-Hui; La, Hank; Malek, Shiva; Purkey, Hans E.; Schaefer, Gabriele; Schmidt, Stephen; et al.
Graphical abstract: Abstract: The treatment of epidermal growth factor receptor (EGFR)-driven non-small cell lung cancers with the T790M resistance mutation remains a significant unmet medical need. We report the identification of 4-aminoindazolyl-dihydrofuro[3, 4- d ]pyrimidines as non-covalent inhibitors of EGFR, with excellent activity against the T790M resistance double mutants and initial single activating mutants. Using an optimization strategy focused on structure-based design and improving PK properties through metabolite identification, we obtained advanced leads with high oral exposure.